A method for producing a continuous carbon fiber reinforced aluminum matrix composite
Patent Information
- Application Number
- CN202611369028.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-04
- Publication Date
- 2026-10-23
AI Technical Summary
[0006]为解决碳纤维表面金属镀层不均匀以及低温条件下铝基体渗浸困难和难以连续化制备的问题,本发明提供一种连续碳纤维增强铝基复合材料的制备方法
(1)本发明通过化学镀镍法在纤维表面涂覆均匀的镍镀层,并掺杂纳米第二相进一步提高纤维导电性,随后采用电镀法在镀镍纤维表面涂覆均匀的铜镀层,解决了电镀铜过程中的“黑芯”现象;最终,将铝粉与表面涂覆铜镍复合镀层的连续碳纤维进行冷喷涂与多道次连续热压烧结,使铝粉渗浸入连续碳纤维单丝间细小的孔隙中。本发明提供的纤维表面改性工艺提高了纤维的导电性,并解决了电镀铜过程中的黑芯现象;同时纤维表面金属化改善了碳纤维与铝合金基体间的润湿性,进一步降低了复合材料制备温度,有效改善了高温液态法制备碳纤维增强铝基复合材料时基体与碳纤维间的剧烈有害反应,并实现连续碳纤维增强铝基复合材料的连续化制备,显著提高了制备效率,得到了高致密度且力学性能优异的连续碳纤维增强铝基复合材料。
Smart Images

Figure CN122959637A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite material preparation technology, and in particular to a method for preparing a continuous carbon fiber reinforced aluminum matrix composite material. Background Technology
[0002] The information disclosed in the background section of this invention is intended only to enhance the understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
[0003] Carbon fiber reinforced aluminum matrix composites possess excellent properties such as high specific strength and high specific modulus, and have broad application prospects in aerospace and rail transportation fields. The performance of these composites depends on the distribution of carbon fibers in the matrix and the quality of interfacial bonding.
[0004] Currently, the preparation of continuous carbon fiber reinforced aluminum matrix composites mostly employs the liquid-phase infiltration method, which involves pressure infiltrating a carbon fiber precast skeleton with molten aluminum at high temperatures. However, the carbon fiber content and spacing are difficult to control precisely during this process, easily leading to fiber segregation. Excessive contact between fibers becomes a crack initiation point, resulting in low-stress brittle fracture. Simultaneously, the interfacial wettability between carbon fibers and the aluminum matrix is extremely poor, making it difficult for molten aluminum to infiltrate into the fiber bundles, often requiring forced infiltration under high temperature or high pressure. High temperatures further exacerbate the harmful reaction that generates a brittle Al4C3 phase at the interface, impairing the intrinsic properties of the fibers.
[0005] Surface metallization is an important means to improve the wettability of carbon fiber / aluminum. Chemical plating can deposit a uniform coating on the fiber surface, but the process is complex, the plating solution is unstable, and the deposition rate is slow. Electroplating is simple and has a fast deposition rate, but for densely packed carbon fiber bundles, uneven electric field distribution can easily lead to a coating that is "thick on the outside and thin on the inside," or even the inside of the fiber bundle may not be coated. This has a significant adverse effect on the infiltration behavior of aluminum melt during the composite material preparation process. Although methods such as hot isostatic pressing can achieve consolidation and forming, the prepared size is limited by the size of the cladding or mold, the forming efficiency is low, and the matrix is still difficult to fully infiltrate in high volume fraction fiber bundles. Summary of the Invention
[0006] To address the problems of uneven metal coating on carbon fiber surfaces and difficulties in impregnating aluminum matrix at low temperatures and the challenges in continuous preparation, this invention provides a method for preparing continuous carbon fiber reinforced aluminum matrix composites.
[0007] In a first aspect, the present invention provides a method for preparing a continuous carbon fiber reinforced aluminum matrix composite material, comprising the following steps: S1: Surface metallization treatment is performed on the continuous carbon fiber. A copper-nickel composite coating is formed on the surface of the continuous carbon fiber by chemical nickel plating and electroplating copper in sequence, to obtain the continuous carbon fiber coated with copper-nickel composite coating. S2: After spreading the continuous carbon fibers coated with the copper-nickel composite layer, aluminum powder is cold-sprayed onto the surface of the continuous carbon fibers to obtain a composite material preform. S3: The composite material preform is pulled into a multi-pass continuous hot pressing sintering device and subjected to multi-pass continuous hot pressing sintering under a protective atmosphere to obtain a continuous carbon fiber reinforced aluminum matrix composite material.
[0008] Preferably, in S1, the continuous carbon fiber is a unidirectional continuous carbon fiber bundle or a carbon fiber woven fabric, and the unidirectional continuous carbon fiber bundle is T300. 3k, T300 6k or T300 12k.
[0009] Preferably, in S1, the plating solution used in the electroless nickel plating method contains 15~35 g / L nickel sulfate, 10~30 g / L sodium hypophosphite and 10~30 mL / L lactic acid; Furthermore, the plating solution also contains a nano-second phase, wherein the nano-second phase is 10 -5 ~10 -3 mol / L carbon nanotubes or 1-15 g graphene.
[0010] Preferably, in S1, the electroless nickel plating method includes the following steps performed in sequence: soaking in acetone solution to remove adhesive for 24-30 hours, ultrasonically treating in degreasing solution at 60-80°C for 20-40 minutes, ultrasonically treating in etching solution at 30-50°C for 5-25 minutes, activating in colloidal palladium activation solution at 10-30°C for 3-7 minutes, immersing in descaling solution for 2-5 minutes, and ultrasonically treating in electroless nickel plating solution at 60-80°C for 30-90 minutes to deposit a nickel plating layer.
[0011] Preferably, the degreasing solution is an aqueous solution containing 50-70 g / L sodium hydroxide, 10-30 g / L sodium carbonate and 30-50 g / L sodium phosphate; The etching solution is an aqueous solution containing 180-220 mL / L nitric acid and 180-220 mL / L sulfuric acid; The colloidal palladium activation solution is an aqueous solution containing 0.3~0.7 g / L palladium chloride, 25~45 g / L stannous chloride, 40~60 mL / L hydrochloric acid, 50~200 g / L sodium chloride and 5~15 g / L pure metallic tin. The degelatinizing solution is an aqueous solution containing 80~120 mL / L hydrochloric acid.
[0012] Preferably, in S1, the copper electroplating method is as follows: using a continuous carbon fiber coated with a nickel layer as the cathode and copper as the anode, immersing it in an electrolyte at 20~40℃, and ultrasonically treating it for 1~4 min under a voltage of 1~3 V, thereby depositing a copper coating on the surface of the nickel-plated carbon fiber; the electrolyte contains 180~220 g / L copper sulfate, 20~40 g / L potassium nitrate and 50~70 g / L sulfuric acid.
[0013] Preferably, in S2, during the cold spraying process, high-pressure gas is used to accelerate aluminum powder to 300-1200 m / s and spray it onto the surface of continuous carbon fiber.
[0014] Preferably, in S3, the protective atmosphere is an argon atmosphere.
[0015] Preferably, in S3, the multi-pass continuous hot pressing sintering includes: first, cold pre-pressing the composite material preform at a pressure of 2~10 MPa, and then heating the composite material preform to 550~620℃ and applying pressure for hot pressing sintering. The hot pressing sintering is a three-pass continuous hot pressing, with the first pass applying a pressure of 5~10 MPa, the second pass applying a pressure of 10~20 MPa, and the third pass applying a pressure of 25~40 MPa. The temperature of the cold pre-compression is room temperature.
[0016] Preferably, the thickness of the continuous carbon fiber reinforced aluminum matrix composite material is 1.0~30.0 mm, and the volume percentage of the continuous carbon fiber in the composite material is 1.0~40.0%. The aluminum powder is pure aluminum powder or aluminum alloy powder.
[0017] Compared with the prior art, the present invention has achieved the following beneficial effects: (1) This invention coats a uniform nickel plating layer onto the fiber surface using a chemical nickel plating method, and further improves the fiber conductivity by doping with a nano-second phase. Subsequently, a uniform copper plating layer is coated onto the nickel-plated fiber surface using an electroplating method, thus solving the "black core" phenomenon in the copper plating process. Finally, aluminum powder and continuous carbon fibers coated with a copper-nickel composite plating layer are cold-sprayed and subjected to multiple continuous hot-pressing sintering processes, allowing the aluminum powder to penetrate into the tiny pores between the continuous carbon fiber monofilaments. The fiber surface modification process provided by this invention improves the fiber conductivity and solves the black core phenomenon in the copper plating process. At the same time, the metallization of the fiber surface improves the wettability between the carbon fiber and the aluminum alloy matrix, further reducing the composite material preparation temperature. This effectively improves the severe harmful reaction between the matrix and carbon fiber when preparing carbon fiber reinforced aluminum matrix composites by the high-temperature liquid method, and realizes the continuous preparation of continuous carbon fiber reinforced aluminum matrix composites, significantly improving the preparation efficiency and obtaining a continuous carbon fiber reinforced aluminum matrix composite with high density and excellent mechanical properties.
[0018] (2) In this application, aluminum powder is first deposited in solid particle form on the surface of the spread continuous carbon fiber to form a preform by cold spraying process. Then, the densification of the preform and the solidification of the composite material are completed in sequence during the process by multiple continuous hot pressing sintering. This breaks through the mold size limitation of traditional hot isostatic pressing or molding process, realizes continuous production, and significantly improves the preparation efficiency. Attached Figure Description
[0019] The accompanying drawings, which form part of this specification, are used to provide a further understanding of the invention. The illustrative embodiments and descriptions of the invention are used to explain the invention and do not constitute an undue limitation thereof. Obviously, those skilled in the art can obtain other drawings based on these drawings without any inventive effort.
[0020] Figure 1 This is a schematic diagram of electroless nickel plating on carbon fiber and a diagram of the surface morphology of carbon fiber after electroless nickel plating. Figure 2 This is a schematic diagram of copper electroplating on the surface of nickel-plated carbon fiber and a diagram of the surface morphology of the carbon fiber after copper electroplating. Figure 3 This is a schematic diagram of the working process for preparing continuous carbon fiber reinforced aluminum matrix composites according to an embodiment of the present invention; Figure 4 This is a microstructure diagram of the cross-section of the carbon fiber reinforced aluminum matrix composite material obtained in Example 4; Figure 5 Comparative Example 2 shows the surface morphology of electroplated copper carbon fibers, where (a) is the morphology of the coating at the core of the fiber bundle, (b) is the morphology of the coating at the edge of the fiber bundle, and (c) is the morphology of the fiber cross section. Figure 6 These are macroscopic surface morphology images of the copper-nickel carbon fiber prepared in Example 1, the nickel-plated carbon fiber prepared in Comparative Example 1, and the electroplated copper carbon fiber prepared in Comparative Example 2. Among them, 1 is nickel plating solution, 2 is continuous carbon fiber bundle, 3 is deposited Ni particles, 4 is ultrasonic vibrator, 5 is anode copper rod, 6 is continuous nickel plating carbon fiber bundle, 7 is deposited Cu particles, 8 is copper plating electrolyte, 9 is continuous carbon fiber, 10 is continuous carbon fiber guide roller, 11 is wire rolling device, 12 is cold spraying device, 13 is cold pressing roll, 14 is cold pressing device pressure sensor, 15 is heating device, 16 is thermal insulation material, 17 is water-cooled hard alloy hot pressing roll, 18 is hot pressing device pressure sensor, 19 is traction device, and 20 is argon atmosphere furnace. Detailed Implementation
[0021] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0022] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] This invention provides a method for preparing continuous carbon fiber reinforced aluminum matrix composite material, comprising the following steps: S1: Surface metallization treatment is performed on the continuous carbon fiber. A copper-nickel composite coating is formed on the surface of the continuous carbon fiber by chemical nickel plating and electroplating copper in sequence, to obtain continuous carbon fiber coated with copper-nickel composite coating. S2: After spreading the continuous carbon fiber coated with copper-nickel composite coating, aluminum powder is cold sprayed onto the surface of the continuous carbon fiber to obtain a composite material preform. S3: The composite material preform is drawn into a multi-pass continuous hot pressing sintering device and subjected to multi-pass continuous hot pressing sintering under a protective atmosphere to obtain a continuous carbon fiber reinforced aluminum matrix composite material.
[0024] Specifically, carbon fiber itself has limited conductivity. If copper is directly electroplated, the difference in electric field distribution inside and outside the fiber bundle can easily lead to a "black core" phenomenon, where the outer coating is thick while the core coating is thin or even unplated. This application first chemically plates a uniform nickel layer on the fiber surface, and then does notopy a nano-second phase (carbon nanotubes or graphene) into the plating solution to synergistically improve the fiber conductivity, making the nickel-plated carbon fiber bundle a uniform conductor as a whole. When copper is electroplated on this basis, the current can be uniformly conducted inside and outside the fiber bundle, thereby obtaining a uniform copper coating on the surface of the nickel-plated fiber, fundamentally solving the "black core" problem of single copper plating.
[0025] The interfacial wettability between carbon fiber and aluminum matrix is extremely poor, making it difficult for molten aluminum to spontaneously infiltrate the fiber bundle. In this application, after constructing a copper-nickel composite coating on the fiber surface, the high-speed impact during cold spraying of aluminum powder can cause plastic deformation and anchoring on the metal coating surface, forming a uniform preform. During subsequent hot-pressing sintering, a solid-state diffusion reaction occurs between the copper coating and the aluminum matrix at the interface. Because the eutectic temperature of the Al-Cu system (548°C) is lower than the melting point of pure aluminum, a local micro-liquid phase can be formed at the interface under process conditions below the liquidus temperature of the aluminum matrix. This liquid phase assists in the densification of aluminum powder particles and promotes their filling of the pores between fiber filaments. The reduction in densification temperature effectively suppresses the harmful reaction that generates brittle Al4C3 between the carbon fiber and the aluminum matrix, protecting the intrinsic structural integrity of the fiber.
[0026] This application first uses cold spraying to deposit aluminum powder in solid form onto the surface of spread continuous carbon fibers to form a preform, avoiding the problem of fiber agglomeration in the melt during liquid preparation, which makes it difficult to control the fiber spacing. Then, through multi-pass continuous hot pressing sintering, the densification of the preform and the consolidation of the composite material are completed sequentially during the process. This breaks through the mold size limitations of traditional hot isostatic pressing or molding processes, realizes continuous production, significantly improves the preparation efficiency, and finally obtains a continuous carbon fiber reinforced aluminum matrix composite material with high density and excellent mechanical properties.
[0027] In some specific embodiments, in S1, the continuous carbon fiber is a unidirectional continuous carbon fiber bundle or a carbon fiber woven fabric, and the unidirectional continuous carbon fiber bundle is T300. 3k, T300 6k or T300 12k.
[0028] Specifically, unidirectional continuous carbon fiber bundles (such as T300) are used. 3k, T300 6k, T300 12k) can prepare high-performance composite materials with unidirectional reinforcement. Using carbon fiber woven fabric makes it easy to achieve two-dimensional or three-dimensional structural reinforcement. This process has good applicability to carbon fibers of different morphologies.
[0029] In some specific embodiments, in S1, the plating solution used in the electroless nickel plating method contains 15~35 g / L nickel sulfate, 10~30 g / L sodium hypophosphite and 10~30 mL / L lactic acid.
[0030] In some specific embodiments, the plating solution also contains a nano-second phase, wherein the nano-second phase is 10 -5 ~10 - 3 mol / L carbon nanotubes or 1-15 g graphene.
[0031] Specifically, on the one hand, the nano-second phase possesses excellent conductivity. During the electroless plating process, it is co-deposited into the nickel plating layer, and the uniformly dispersed nano-carbon materials form a three-dimensional conductive network within the plating layer, significantly improving the overall conductivity of the nickel plating layer. On the other hand, the nano-size effect of carbon nanotubes or graphene can also refine the grain structure of the nickel plating layer, reduce the porosity of the plating layer, and improve the density of the plating layer. The improved conductivity of the plating layer makes the nickel-plated carbon fiber bundles a uniform conductor as a whole, providing a uniform current-conducting substrate for subsequent copper electroplating, thereby ensuring the uniform deposition of the copper plating layer inside and outside the fiber bundles.
[0032] In some specific embodiments, in S1, the electroless nickel plating method includes the following steps performed in sequence: soaking in acetone solution to remove adhesive for 24-30 hours, ultrasonically treating in degreasing solution at 60-80°C for 20-40 minutes, ultrasonically treating in etching solution at 30-50°C for 5-25 minutes, activating in colloidal palladium activation solution at 10-30°C for 3-7 minutes, immersing in descaling solution for 2-5 minutes, and ultrasonically treating in electroless nickel plating solution at 60-80°C for 30-90 minutes to deposit a nickel plating layer.
[0033] Specifically, degumming and degreasing remove the original coating and contaminants from the fiber surface, etching improves the surface roughness and surface activity of the fiber, colloidal palladium activation and degumming form uniform catalytic active sites on the fiber surface, and the coordinated efforts of each process ensure that the nickel plating layer can be deposited continuously and uniformly.
[0034] In some specific embodiments, the degreasing solution is an aqueous solution containing 50-70 g / L sodium hydroxide, 10-30 g / L sodium carbonate and 30-50 g / L sodium phosphate; The etching solution is an aqueous solution containing 180-220 mL / L nitric acid and 180-220 mL / L sulfuric acid; The colloidal palladium activation solution is an aqueous solution containing 0.3~0.7 g / L palladium chloride, 25~45 g / L stannous chloride, 40~60 mL / L hydrochloric acid, 50~200 g / L sodium chloride and 5~15 g / L pure metallic tin. The degelatinizing solution is an aqueous solution containing 80~120 mL / L hydrochloric acid.
[0035] Specifically, the degreasing solution uses sodium hydroxide, sodium carbonate, and sodium phosphate to remove contaminants; the etching solution uses nitric acid and sulfuric acid to coarse the fiber surface without damaging the fiber itself; the activation solution uses palladium chloride to provide a catalytic core, and stannous chloride to stabilize colloidal palladium and maintain its dispersibility; and the descaling solution removes residual tin compounds and exposes the active palladium core.
[0036] In some specific embodiments, in S1, the copper electroplating method is as follows: using a continuous carbon fiber coated with a nickel layer as the cathode and copper as the anode, immersing it in an electrolyte at 20~40℃, and ultrasonically treating it for 1~4 min under a voltage of 1~3 V, thereby depositing a copper coating on the surface of the nickel-plated carbon fiber; the electrolyte contains 180~220 g / L copper sulfate, 20~40 g / L potassium nitrate and 50~70 g / L sulfuric acid.
[0037] Specifically, copper sulfate provides copper ions, sulfuric acid enhances conductivity and prevents hydrolysis, and potassium nitrate improves dispersion and coverage; low voltage avoids hydrogen evolution side reactions, and ultrasonic treatment promotes the renewal of the plating solution and ion migration inside the fiber bundle; mild temperature and short treatment time balance coating quality and preparation efficiency.
[0038] In some specific embodiments, in S2, during the cold spraying process, high-pressure gas is used to accelerate aluminum powder to 300-1200 m / s and spray it onto the surface of continuous carbon fiber.
[0039] Specifically, aluminum powder impacts the fiber surface at a high speed of 300~1200 m / s, causing plastic deformation and anchoring to the metal coating surface, thus achieving a mechanical bond between the aluminum matrix and carbon fiber. Preform formation can be completed without high temperature, avoiding thermal damage to the fiber.
[0040] In some specific embodiments, in S3, the protective atmosphere is an argon atmosphere.
[0041] Specifically, the argon atmosphere isolates reactive gases such as oxygen and nitrogen during the hot pressing process, avoiding high-temperature oxidation of aluminum powder and carbon fiber, thus ensuring a clean interface.
[0042] In some specific embodiments, in S3, the multi-pass continuous hot pressing sintering includes: first, cold pre-pressing the composite material preform at a pressure of 2~10 MPa, and then heating the composite material preform to 550~620℃ and applying pressure for hot pressing sintering. The hot pressing sintering is a three-pass continuous hot pressing, with the first pass applying a pressure of 5~10 MPa, the second pass applying a pressure of 10~20 MPa, and the third pass applying a pressure of 25~40 MPa. The temperature of the cold pre-compression is room temperature.
[0043] Specifically, the cold pre-compression treatment of 2~10 MPa initially densifies the loose preform after cold spraying, eliminating large gaps between aluminum powder particles and between the powder and fiber interfaces, while avoiding damage to the fibers due to excessive pressure. The heating temperature of 550~620℃ is selected based on the eutectic temperature of the Al-Cu system (548℃): this temperature range is higher than the Al-Cu eutectic point but lower than the melting point of pure aluminum (660℃) and the liquidus temperature of common aluminum alloys. This allows the copper plating on the fiber surface to diffuse and react with the aluminum matrix at the interface to form a local micro-liquid phase. This liquid phase assists in the densification of solid aluminum powder particles and fills the pores between fiber filaments, while avoiding harmful interfacial reactions (forming brittle Al4C3) between carbon fibers and the aluminum matrix caused by excessively high temperatures. The gradient pressurization strategy, which applies pressure in three stages (5~10 MPa→10~20 MPa→25~40 MPa), avoids damage to the fiber structure caused by sudden high pressure. At the same time, it allows residual gas inside the composite material to be gradually discharged during the pressure progression, which is conducive to obtaining high-density composite materials. The densification of the preform and the consolidation of the composite material are completed during the continuous process, breaking through the mold size limitations of traditional hot isostatic pressing or molding processes.
[0044] In some specific embodiments, the present invention does not impose special limitations on the multi-pass continuous hot pressing sintering apparatus, as long as it can provide an argon protective atmosphere, segmented heating function, and multi-pass step-by-step pressurization capability. For example... Figure 3 As shown, the multi-pass continuous hot pressing sintering apparatus includes a cold pressing roll 13, a heating device 15, and at least three hot pressing rolls arranged sequentially along the continuous carbon fiber traveling direction. The hot pressing rolls are preferably water-cooled hard alloy rolls 17 to avoid roll deformation at high temperatures. The cold pressing rolls are used to apply a pressure of 2~10 MPa to the composite material preform for cold pre-pressing. The heating device 15 is used to heat the preform after cold pre-pressing to 550~620℃ and keep it at that temperature. Insulation material 16 can be set on the outer periphery of the heating device to reduce heat loss and ensure temperature uniformity in the furnace. The hot pressing rolls are arranged sequentially, and the applied pressure of each pass of the hot pressing rolls increases step by step, and the roll spacing of each pass of the hot pressing rolls decreases step by step to achieve gradient pressurization and densification during the travel process. The multi-pass continuous hot pressing sintering device is also equipped with an argon atmosphere furnace body 20 to isolate active gases such as oxygen and nitrogen during the hot pressing process, thereby avoiding high-temperature oxidation of aluminum powder and high-temperature oxidation damage to carbon fibers; a traction device 19 is provided at the end of the device to continuously remove the composite material sample that has completed hot pressing sintering, thereby realizing the continuous preparation of continuous carbon fiber reinforced aluminum matrix composite material.
[0045] In some specific embodiments, the thickness of the continuous carbon fiber reinforced aluminum matrix composite material is 1.0~30.0 mm, and the volume percentage of the continuous carbon fiber in the composite material is 1.0~40.0%. The aluminum powder is pure aluminum powder or aluminum alloy powder.
[0046] The present invention will be further described in detail below with reference to specific embodiments. It should be noted that the specific embodiments are for explanation and not limitation of the present invention. Unless otherwise specified, the experimental methods described in the following embodiments are conventional methods; unless otherwise specified, the reagents and materials are commercially available.
[0047] Example 1 This embodiment provides a method for preparing carbon fiber surface metallization, specifically including the following steps: Carbon fibers were placed in acetone solution and allowed to stand at room temperature for 24 h to remove the epoxy resin coating from the carbon fiber surface. The degummed carbon fibers were then immersed in a degreasing solution (an aqueous solution containing 60 g / L sodium hydroxide, 20 g / L sodium carbonate, and 40 g / L sodium phosphate) and ultrasonically treated at 65 °C for 20 min. The degummed carbon fibers were then immersed in an etching solution (an aqueous solution containing 200 mL / L nitric acid and 200 mL / L sulfuric acid) and ultrasonically treated at 50 °C for 20 min. The etched carbon fibers were then immersed in a colloidal palladium activation solution (an aqueous solution containing 0.5 g / L palladium chloride, 35 g / L stannous chloride, 50 mL / L hydrochloric acid, and 178 g / L sodium chloride) at room temperature for 7 min. After colloidal palladium activation treatment, the carbon fibers were immersed in a degumming solution (an aqueous solution containing 100 mL / L hydrochloric acid) at 40 °C for 5 min. The activated and degummed carbon fibers were placed in a plating solution (an aqueous solution of 25 g / L nickel sulfate, 20 g / L sodium hypophosphite, and 20 mL / L lactic acid) and ultrasonically treated at 70°C for 90 min to deposit a nickel plating layer on the carbon fiber surface. Using the nickel-plated carbon fiber bundle as the cathode and copper as the anode, the fiber was immersed in an electrolyte solution (an aqueous solution of 200 g / L copper sulfate, 30 g / L potassium nitrate, and 60 g / L sulfuric acid) at 35°C and ultrasonically treated at 2 V for 3 min to deposit a copper plating layer on the surface of the nickel-plated carbon fiber. The resulting carbon fiber was designated Cu / Ni-CF. After each step in the above process, the fiber was rinsed three times with deionized water. After the deposition treatment, the fiber was completely dried in a vacuum drying oven.
[0048] Example 2 This embodiment provides a method for preparing carbon fiber surface metallization doped with carbon nanotubes, which differs from Example 1 in that the electroless nickel plating solution also contains 10 -4 mol / L carbon nanotubes.
[0049] The specific steps are basically the same as in Example 1, except that the activated and degummed carbon fibers are placed in a plating bath (composed of 25 g / L nickel sulfate, 20 g / L sodium hypophosphite, 20 mL / L lactic acid, and 10 g / L sodium hypophosphite). -4 The carbon fibers were immersed in an aqueous solution of carbon nanotubes (mol / L) and ultrasonically treated at 70°C for 90 min to deposit a nickel plating layer of carbon nanotubes on the surface of the carbon fibers. Subsequently, the carbon fibers were treated under the same copper electroplating conditions as in Example 1.
[0050] Example 3 This embodiment provides a method for preparing graphene-doped carbon fiber surface metallization, which differs from Example 1 in that the electroless nickel plating solution also contains 5 g / L of graphene.
[0051] The specific steps are basically the same as in Example 1, except that the activated and degummed carbon fibers are placed in a plating solution (composed of an aqueous solution of 25 g / L nickel sulfate, 20 g / L sodium hypophosphite, 20 mL / L lactic acid, and 5 g / L graphene) and ultrasonically treated at 70°C for 90 min to deposit a graphene-doped nickel plating layer on the carbon fiber surface. Subsequently, the copper electroplating is performed under the same conditions as in Example 1.
[0052] Example 4 This embodiment provides a method for preparing a continuous carbon fiber reinforced aluminum matrix composite material, using the continuous carbon fiber coated with a copper-nickel composite layer prepared in Example 1 as the raw material.
[0053] Twelve continuous carbon fiber bundles were spread using a fiber-rolling device and then drawn into a cold spraying device. Pure aluminum powder was sprayed onto the surface of the continuous fibers at a speed of 600 m / s to obtain a composite material preform. The preform was then drawn into a multi-pass continuous hot-pressing sintering device under argon protection. First, the preform was cold-pre-pressed at a pressure of 5 MPa at room temperature. Then, it was drawn into a furnace at 600℃ for heating and holding. Subsequently, pressures of 10 MPa, 15 MPa, and 20 MPa were applied in three passes, with pressure roller spacings of 20 mm, 15 mm, and 10 mm, respectively. Finally, the continuous carbon fiber reinforced aluminum matrix composite sample was continuously removed through a traction device.
[0054] Example 5 This embodiment provides a method for preparing a continuous carbon fiber reinforced aluminum matrix composite material. The difference between this method and Example 4 is that the copper-nickel composite coated carbon fiber with carbon nanotube doping prepared in Example 2 is used as the raw material, and the hot pressing sintering process is the same as in Example 4.
[0055] Twelve continuous carbon fiber bundles were spread and drawn into a cold spraying device, where pure aluminum powder was sprayed onto the surface of the continuous fibers at a speed of 600 m / s to obtain a composite material preform. The preform was then drawn into a multi-pass continuous hot-pressing sintering device under argon protection. First, the preform was cold-pre-pressed at a pressure of 5 MPa at room temperature. Then, it was drawn into a furnace at 600℃ for heating and holding. Subsequently, pressures of 10 MPa, 15 MPa, and 20 MPa were applied in three passes, with pressure roller spacing of 20 mm, 15 mm, and 10 mm respectively. Finally, the sample was continuously removed through a traction device.
[0056] Example 6 This embodiment provides a method for preparing a continuous carbon fiber reinforced aluminum matrix composite material, which differs from Example 4 in that: the graphene-doped copper-nickel composite coated carbon fiber prepared in Example 3 is used as the raw material, and the hot pressing sintering process is the same as in Example 4.
[0057] Twelve continuous carbon fiber bundles were spread and drawn into a cold spraying device, where pure aluminum powder was sprayed onto the surface of the continuous fibers at a speed of 600 m / s to obtain a composite material preform. The preform was then drawn into a multi-pass continuous hot-pressing sintering device under argon protection. First, the preform was cold-pre-pressed at a pressure of 5 MPa at room temperature. Then, it was drawn into a furnace at 600℃ for heating and holding. Subsequently, pressures of 10 MPa, 15 MPa, and 20 MPa were applied in three passes, with pressure roller spacing of 20 mm, 15 mm, and 10 mm respectively. Finally, the sample was continuously removed through a traction device.
[0058] Comparative Example 1 This comparative example provides a method for preparing a nickel-plated carbon fiber reinforced aluminum matrix composite material, specifically including: The degummed carbon fibers were subjected to the same chemical nickel plating treatment as in Example 1, except that the plating solution did not contain a nano-second phase, resulting in nickel-plated carbon fibers, denoted as Ni-CF. Subsequently, nickel-plated carbon fiber reinforced aluminum matrix composites were prepared under the same preparation conditions as in Example 4 (hot pressing temperature of 600°C, three-pass pressure of 10 MPa, 15 MPa, and 20 MPa).
[0059] Comparative Example 2 This comparative example provides a method for preparing an electroplated copper carbon fiber reinforced aluminum matrix composite material, specifically including: The degummed carbon fibers were directly subjected to the same electroplating copper treatment as in Example 1, except that they were not electroless nickel plating, resulting in copper-plated carbon fibers, denoted as Cu-CF. Subsequently, copper-plated carbon fiber reinforced aluminum matrix composites were prepared under the same preparation conditions as in Example 4 (hot pressing temperature of 600°C, three-pass pressure of 10 MPa, 15 MPa, and 20 MPa).
[0060] Comparative Example 3 This comparative example provides a method for preparing a chemically plated copper carbon fiber reinforced aluminum matrix composite material, specifically including: Chemical copper plating was performed on the degummed carbon fiber: The degummed carbon fiber was sequentially subjected to degreasing, roughening (50 g / L sulfuric acid + 200 g / L ammonium persulfate, ultrasonication at 35℃ for 15 min), sensitization (15 g / L SnCl2 + 40 mL / L HCl, ultrasonication for 30 min), and activation (0.5 g / L PdCl2 + 10 mL / L HCl, ultrasonication at 50℃ for 30 min). Then, it was placed in a chemical copper plating solution (15 g / L CuSO4 + 30 mL / L HCHO + 5 g / L EDTA-2Na + 25 g / L NaKC4H4O6) and ultrasonicated at 50℃ for 20 min to deposit a copper plating layer on the fiber surface. Subsequently, a preform was prepared under the same cold spraying conditions as in Example 4, and then hot-pressed and sintered at 650℃ and three passes at pressures of 10 MPa, 20 MPa, and 30 MPa.
[0061] Comparative Example 4 This comparative example provides a method for preparing copper-nickel composite coated carbon fiber reinforced aluminum matrix composite materials using traditional powder metallurgy, specifically including: The continuous carbon fibers coated with a copper-nickel composite layer prepared in Example 1 were used as raw materials. Twelve bundles of continuous carbon fibers were cut into short fibers (approximately 5-10 mm in length). Then, following the same carbon fiber volume fraction (approximately 5-10 vol.%) as in Example 4, the short carbon fibers were mechanically mixed with pure aluminum powder in a V-type mixer for 60 min to ensure initial homogeneity. The mixed material was placed in a steel mold and cold-pressed at 5 MPa at room temperature to obtain a cold-pressed preform. The cold-pressed preform was then placed in a graphite mold and placed in a hot-pressing sintering furnace. Under an argon protective atmosphere, it was heated to 600°C, then subjected to a pressure of 20 MPa and held at that temperature for 60 min. After cooling in the furnace, the sample was removed to obtain a carbon fiber reinforced aluminum matrix composite material.
[0062] Comparative Example 5 This comparative example provides a method for preparing copper-nickel composite coated carbon fiber reinforced aluminum matrix composite materials using single-pass hot pressing sintering, specifically including: Using the continuous carbon fiber coated with a copper-nickel composite layer prepared in Example 1 as raw material, a preform was prepared under the same cold spraying conditions as in Example 4, and then subjected to single-pass hot pressing sintering: under argon protection, the preform was heated to 600°C and then a pressure of 20 MPa was directly applied. After holding the pressure for a certain period of time, the sample was removed. The total hot pressing pressure (20 MPa) was the same as the final pressure of the three passes in Example 4, but the pressure was applied in one pass.
[0063] Comparative Example 6 This comparative example provides a method for preparing composite materials by direct hot pressing without cold pre-pressing after cold spraying, specifically including: Using the continuous carbon fiber coated with copper-nickel composite layer prepared in Example 1 as raw material, a preform was prepared under the same cold spraying conditions as in Example 4, but the preform was directly drawn into the heating furnace and subjected to three consecutive hot pressing sintering at 600°C without cold pre-pressing (pressure conditions were the same as in Example 4).
[0064] Experimental Example 1: Observation of Coating Morphology and Testing of Fiber Conductivity The coating morphology of the surface-metallized carbon fibers prepared in Examples 1-3 and Comparative Examples 1-3 was observed, and the results are shown in Table 1. The conductivity of the original carbon fibers and the surface-metallized carbon fibers prepared in Examples 1-3 was tested, and the results are shown in Table 2.
[0065] Table 1. Diameter of carbon fibers prepared by different surface treatment processes
[0066] Table 2. Conductivity of nickel-plated carbon fibers prepared by different surface treatment processes
[0067] As shown in Table 1, the copper-nickel composite coatings prepared by the electroless nickel plating + electroplating copper composite process in Examples 1-3 are uniform and continuous, with small fluctuations in fiber diameter (standard deviation ≤ 0.7 μm). In Examples 2 and 3, due to the introduction of carbon nanotubes and graphene nanophases into the electroless nickel plating solution, the coating thickness was slightly increased, with fiber diameters reaching 12.0 ± 0.7 μm and 11.7 ± 0.6 μm, respectively, indicating successful co-deposition of the nanophases in the nickel coating. In contrast, the fiber diameter of Comparative Example 1 (single electroless nickel plating) was only 9.4 ± 0.6 μm, the coating of Comparative Example 3 (single electroless copper plating) was thinner and had poorer uniformity (diameter fluctuation of ± 1.0 μm), while Comparative Example 2 (direct electroplating copper) had the largest fiber diameter fluctuation (± 1.6 μm), reflecting extremely uneven distribution of the coating inside and outside the fiber bundle, confirming the negative impact of the "black core" phenomenon on coating consistency.
[0068] As shown in Table 2, the conductivity of the original degummed carbon fiber was only 1.0 kS / cm. After electroless nickel plating, the conductivity of the nickel-plated fiber bundle in Example 1 increased significantly to 10.9 kS / cm, approximately 10.9 times that of the original fiber. Based on this, Examples 2 and 3 further increased the conductivity to 11.7 kS / cm and 12.1 kS / cm, respectively, by further doping carbon nanotubes or graphene into the nickel plating layer. This indicates that the nano-second phase forms a three-dimensional conductive network in the plating layer, effectively reducing contact resistance and further improving the overall conductivity of the fiber bundle. This provides a better conductive substrate for the uniform conduction of current inside and outside the fiber bundle during subsequent copper plating, thus ensuring the uniform deposition of the copper plating layer in the core and edges of the fiber bundle.
[0069] The surface morphology of the nickel-plated carbon fiber prepared in Example 1 is as follows: Figure 1 As shown, the coating on the carbon fiber surface is uniform and continuous, with no agglomeration. The conductivity of the nickel-plated carbon fiber bundle (10.9 kS / cm) is approximately 10.9 times that of the degummed carbon fiber (1.0 kS / cm). The improved conductivity of the nickel-plated carbon fiber bundle provides a uniform and efficient current-conducting substrate for the copper electroplating process.
[0070] The directly electroplated copper carbon fiber prepared in Comparative Example 2, such as Figure 5 As shown, a distinct "black core" phenomenon appears in the fiber bundle core. Figure 5 (a) The coating at the edge of the fiber bundle is thicker ( Figure 5 (b) The coating uniformity is poor, and the fiber diameter fluctuates greatly (10.5±1.6 μm). This indicates that when copper is electroplated directly without a chemical nickel underlayer, the uneven distribution of the electric field inside and outside the fiber bundle results in a coating that is "thicker on the outside and thinner on the inside," meaning that the individual filaments inside the fiber bundle are not fully coated. Therefore, there are a large number of unfilled defects in the composite material.
[0071] Cross-sectional microstructure of the continuous carbon fiber reinforced aluminum matrix composite obtained in Example 4 was observed. Figure 4 The results showed that the aluminum matrix fully filled the tiny pores between the carbon fiber monofilaments, and the fiber-matrix interface was well bonded with no obvious pores or cracks.
[0072] Experimental Example 2: Mechanical Properties and Density Testing of Composite Materials The tensile strength and relative density of the continuous carbon fiber reinforced aluminum matrix composites prepared in Examples 4-6 and Comparative Examples 1-6 were tested. The tensile strength was tested according to the method disclosed in standard GB / T 228.1-2010, and the results are shown in Table 3.
[0073] Table 3 Mechanical properties and density of composite materials obtained by different preparation processes
[0074] As shown in Table 3: In Examples 4-6, the composite materials prepared by the copper-nickel composite coating + cold pre-pressing + three-pass continuous hot pressing process achieved a tensile strength of 142-147 MPa and a relative density of 98.1%-98.8%, which were significantly better than the comparative examples.
[0075] The mechanical properties of Comparative Example 1 (89±3 MPa) were significantly lower than those of Example 4 (142±1 MPa). This is because the solidus temperature of the Al-Cu system (548℃) is much lower than that of the Al-Ni system (640℃). Nickel-plated carbon fibers cannot form localized micro-liquid phases for impregnation at 600℃, resulting in a large number of unfilled defects in the composite material, thus leading to poor mechanical properties and a relative density of only 95.8%. In contrast, in Example 4, the copper plating and the aluminum substrate could form localized Al-Cu micro-liquid phases at 600℃, promoting the impregnation behavior of the aluminum substrate and achieving a relative density of 98.8%.
[0076] Comparative Example 2 exhibited the lowest mechanical properties (66±6 MPa). Combined with Experimental Example 1, it can be seen that direct copper plating treatment easily leads to a "black core" phenomenon in the fiber bundle. Figure 6 The coating has poor uniformity, and the individual filaments inside the fiber bundle are not fully coated, which prevents the aluminum matrix from penetrating into the fiber bundle core, resulting in a large number of unfilled defects in the composite material.
[0077] Comparative Example 3 required a higher hot-pressing temperature (650°C), and its tensile strength (132±3 MPa) was lower than that of Example 4 (142±1 MPa). This is because the electroless copper plating layer was thinner and the uniformity of the plating thickness inside and outside the fiber bundle was poor (fiber diameter 8.2±1.0 μm). The copper content was insufficient to form a sufficient Al-Cu local micro-liquid phase at the interface, thus requiring a higher hot-pressing temperature. However, the high temperature exacerbated the harmful interfacial reaction and affected the performance of the composite material.
[0078] Comparative Example 4, prepared using conventional powder metallurgy, exhibited lower tensile strength (125±3 MPa) and relative density (97.5%) compared to Example 4. This is because while chopped fibers can achieve a certain degree of densification during mixing and pressing, the fiber length is limited, preventing the full realization of the long-range load-bearing reinforcement effect of continuous fibers. Furthermore, the uniformity of fiber dispersion and the controllability of orientation in the matrix are inferior to the continuous spreading-cold spraying process of this invention. Additionally, conventional powder metallurgy involves complex processes and low preparation efficiency, making continuous production impossible.
[0079] Comparative Example 5 used a single-pass hot pressing (applying 20 MPa at once) instead of three-pass continuous gradient pressing. The tensile strength (135±2 MPa) and relative density (97.7%) of the resulting composite material were both lower than those of Example 4 (142±1 MPa, 98.8%). This is because when a single-pass high pressure is applied abruptly, the residual gas in the preform cannot be gradually discharged during the pressure progression and is easily trapped inside the material, forming micropores. At the same time, instantaneous high pressure loading can easily cause local stress concentration and structural damage to the fiber bundles, resulting in the fiber reinforcement effect not being fully realized. In contrast, the three-pass gradient pressing strategy of Example 4 allows the gas to be discharged step by step, the matrix to be gradually densified, and fiber damage to be avoided, thus achieving higher mechanical properties and density.
[0080] Comparative Example 6, which underwent three rounds of hot pressing directly after cold spraying without cold pre-pressing, also showed lower tensile strength (137±2 MPa) and relative density (97.9%) compared to Example 4. This is because after cold spraying, numerous loose pores exist between aluminum powder particles and at the powder-fiber interface within the preform. Without initial compaction through cold pre-pressing, directly heating to 600°C for hot pressing makes it difficult to completely eliminate the oxide film and closed pores between particles during subsequent hot pressing. This results in numerous residual pore defects in the final composite material, thereby reducing interfacial bonding strength and overall density. This result confirms that the cold pre-pressing step plays an irreplaceable role in eliminating large-sized pores and ensuring the subsequent hot pressing densification effect.
[0081] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a continuous carbon fiber reinforced aluminum matrix composite material, characterized in that, Includes the following steps: S1: Surface metallization treatment is performed on the continuous carbon fiber. A copper-nickel composite coating is formed on the surface of the continuous carbon fiber by chemical nickel plating and electroplating copper in sequence, to obtain continuous carbon fiber coated with copper-nickel composite coating. S2: After spreading the continuous carbon fibers coated with the copper-nickel composite layer, aluminum powder is cold-sprayed onto the surface of the continuous carbon fibers to obtain a composite material preform. S3: The composite material preform is pulled into a multi-pass continuous hot pressing sintering device and subjected to multi-pass continuous hot pressing sintering under a protective atmosphere to obtain a continuous carbon fiber reinforced aluminum matrix composite material.
2. The method for preparing continuous carbon fiber reinforced aluminum matrix composite material according to claim 1, characterized in that, In S1, the continuous carbon fiber is a unidirectional continuous carbon fiber bundle or a carbon fiber woven fabric, and the unidirectional continuous carbon fiber bundle is T300. 3k, T300 6k or T300 12k.
3. The method for preparing continuous carbon fiber reinforced aluminum matrix composite material according to claim 1, characterized in that, In S1, the plating solution used in the electroless nickel plating method contains 15~35 g / L nickel sulfate, 10~30 g / L sodium hypophosphite and 10~30 mL / L lactic acid; Furthermore, the plating solution also contains a nano-second phase, wherein the nano-second phase is 10 -5 ~10 -3 mol / L carbon nanotubes or 1-15 g graphene.
4. The method for preparing continuous carbon fiber reinforced aluminum matrix composite material according to claim 1, characterized in that, In S1, the electroless nickel plating method includes the following steps performed in sequence: soaking in acetone solution to remove adhesive for 24-30 hours, ultrasonic treatment in degreasing solution at 60-80°C for 20-40 minutes, ultrasonic treatment in etching solution at 30-50°C for 5-25 minutes, activation in colloidal palladium activation solution at 10-30°C for 3-7 minutes, immersion in descaling solution for 2-5 minutes, and ultrasonic treatment in electroless nickel plating solution at 60-80°C for 30-90 minutes to deposit a nickel plating layer.
5. The method for preparing continuous carbon fiber reinforced aluminum matrix composite material according to claim 4, characterized in that, The degreasing solution is an aqueous solution containing 50-70 g / L sodium hydroxide, 10-30 g / L sodium carbonate and 30-50 g / L sodium phosphate; The etching solution is an aqueous solution containing 180-220 mL / L nitric acid and 180-220 mL / L sulfuric acid; The colloidal palladium activation solution is an aqueous solution containing 0.3~0.7 g / L palladium chloride, 25~45 g / L stannous chloride, 40~60 mL / L hydrochloric acid, 50~200 g / L sodium chloride and 5~15 g / L pure metallic tin. The degelatinizing solution is an aqueous solution containing 80~120 mL / L hydrochloric acid.
6. The method for preparing continuous carbon fiber reinforced aluminum matrix composite material according to claim 1, characterized in that, In S1, the copper electroplating method is as follows: using continuous carbon fibers coated with nickel as the cathode and copper as the anode, immersing them in an electrolyte at 20~40℃, and ultrasonically treating them for 1~4 min under a voltage of 1~3 V, thereby depositing a copper coating on the surface of the nickel-plated carbon fibers; the electrolyte contains 180~220 g / L copper sulfate, 20~40 g / L potassium nitrate and 50~70 g / L sulfuric acid.
7. The method for preparing continuous carbon fiber reinforced aluminum matrix composite material according to claim 1, characterized in that, In S2, during the cold spraying process, high-pressure gas is used to accelerate aluminum powder to 300-1200 m / s and spray it onto the surface of continuous carbon fiber.
8. The method for preparing continuous carbon fiber reinforced aluminum matrix composite material according to claim 1, characterized in that, In S3, the protective atmosphere is an argon atmosphere.
9. The method for preparing continuous carbon fiber reinforced aluminum matrix composite material according to claim 1, characterized in that, In S3, the multi-pass continuous hot pressing sintering includes: first, cold pre-pressing the composite material preform at a pressure of 2~10 MPa, then heating the composite material preform to 550~620℃ and applying pressure for hot pressing sintering. The hot pressing sintering is a three-pass continuous hot pressing, with the first pass applying a pressure of 5~10 MPa, the second pass applying a pressure of 10~20 MPa, and the third pass applying a pressure of 25~40 MPa. The temperature of the cold pre-compression is room temperature.
10. The method for preparing the continuous carbon fiber reinforced aluminum matrix composite material according to claim 1, characterized in that, The thickness of the continuous carbon fiber reinforced aluminum matrix composite material is 1.0~30.0 mm, and the volume percentage of the continuous carbon fiber in the composite material is 1.0~40.0%. The aluminum powder is pure aluminum powder or aluminum alloy powder.